From Mental Phenomena to Propositional Attitudes: Brentano, Russell, and Chisholm on Intentionality - Niel, Luis Ignacio (2022)
The article presents a historical but mainly conceptual comparison of two(quite) different views of intentionality: one introduced by Franz Brentano and basedon a descriptive- psychological perspective of mental life, and another conducted byRoderick Chisholm and ruled by a logico-linguistic viewpoint. In spite of Chisholm’scontinuous references to Brentano, I will claim that the former conceptually breaks withthe latter, as he introduces several (clearly non-Brentanian) conceptual tools mainlyborrowed from Bertrand Russell’s philosophy, which exerted a decisive influence onsome theoretical decisions taken by Chisholm. This is the case, for instance, of usingthe (Russellian) concept of propositional attitudes for understanding intentionality. Iwill argue that this interpretation is based on a strong logico-linguistic commitment,which is not merely a methodological strategy, but it is also grounded on a fully differentphilosophical standpoint other than the one first inaugurated by Brentano.